Um modelo multimodal para a abordagem didática de textos imagéticos: uma proposta para o letramento visual no ensino de língua portuguesa - Pinto , Ana Cláudia Soares (2016)
The discursive multimodality is a common linguistic phenomenon to any genre, and it is the union of more than one semiotic resource in a enunciation event. It is something that requires an understanding of semiotic materiality of texts paying attention to the understanding of all resources used in its constitution. It is something that requires a comprehension of semiotic materiality of texts paying attention to the understanding of all resources used in its constitution. Thus, this research focuses on such epistemological approach and it has as principal goal to investigate the implementation of a multimodal model as didactic proposal to the approach of the multimodal genres in Portuguese Language Teaching. Thus, this research focuses on this epistemological approach and aims to investigate the implementation of a multimodal model as didactic proposal to address the multimodal genres in Portuguese Language Teaching classes. The central object of the investigation is a field research developed in a class of ninth year of the Primary School in a public school in collaboration with the titular teacher of the cited class. The generation of data corresponded to three specific moments: the sequences of lessons, which consists in the planning and realization of the didactic project with the multimodal genres; the oral and written texts produced by the collaborator teacher about her participation in the research; and the textual productions of the students of the investigated class.The central object of this presente research is a research developed in a class of ninth year in a public school, that was done with the collaboration of the teacher of that class. The research data is based on three specific moments: the sequences of lessons, which is the planning and realization of the educational project with multimodal genres; oral and written texts produced by the titular teacher about her participation in the research; and textual productions of the students of the investigated group. Based on multimodal theoretical model, a sequence of three classes were developed and applied, in order to develop visual literacy. The main results point to the identification of multimodal model as an essential educational tool in the visual literacy process to develop a educational attainment. This fact leads to another: the perception of a critical and more aware use of language materialized by the interaction of verbal and image in the student productions. In addition, evaluations of own pedagogical, made by the titular teacher, demostrated a positive assessment performed experience while also unveil epistemological difficulties during the research. Therefore, we can state the positive contribution of the multimodal teaching project to approach a practice of reading and production of imagistic texts in a socially conscious way. This fact corraborate to the thesis that participation in an educational project through multimodal model enables contact with aspects of the production of multimodal genres and with its own meta-language developing Visual Literacy and critical training learner.